EFEKTIFITAS PENERAPAN KEPEMIMPINAN PEMBELAJARAN KEPALA SEKOLAH PADA SMK BIDANG MANAJEMEN BISNIS/PARIWISATA - SAMSORI, SAMSORI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
The research was carried out in three schools as case studies, it is hoped that it can describe the characteristics of learning leadership in best practice schools in the area. Using a qualitative approach, this research explores learning leadership in depth through interview methods, observation and documentation studies. The principal as a learning leader develops an academic culture starting from a school vision worth working professionalism. The vision presented forms an acronym; easy to memorize, like IDEAL (Innovative, Educative and Professional). The school principal is committed to communicating the vision and mission of the school's goals through: 1) professional visualization, 2) various socialization programs, 3) communicative approach, 4) acting as a model of character (commitment; trustworthy; tough; firm and brave; working hard, sincere and intelligent; social mission; visionary; reliable and religious lobbyist). The principal develops a learning climate through: 1) time commitment and discipline; 2) building superior characters, 3) character formation policies; 4) achievement potential learning climate; 5) professional work climate; 6) be present around interacting with students; 7) greetings and greetings in various activities. The school principal develops a learning program starting with providing an example of being a professional educator - teaching like a teacher, committed to carrying out supervision, facilitating various academic activities and continuous teacher professional development (IHT, MGMP, Workshops). The school principal is committed to attaching importance to himself: being present, involved and interacting at every opportunity, as a form of providing attention and support. ABSTRAKPenelitian dilaksanakan di tiga sekolah sebagai studi kasus, diharapkan dapat menggambarkan karakteristik kepemimpinan pembelajaran di sekolah best practice di daerahnya. Dengan menggunakan pendekatan kualitatif, penelitian ini menggali secara mendalam kepemimpinan pembelajaran melalui metode wawancara, observasi dan studi dokumentasi. Kepala sekolah sebagai pemimpin pembelajaran mengembangkan budaya akademik dimulai dari visi sekolah bernilai profesionlitas kerja. Visi disajikan membentuk akronim; mudah dihapal, seperti IDEAL (Inovatif, Edukatif dan Profesional). Kepala sekolah berkomitmen mengkomunikasikan visi-misi tujuan sekolah melalui : 1) visualisasi profesional, 2) berbagai program sosialisasi, 3) pendekatan komunikatif, 4) berperan model berkarakter (komitmen; dipercaya; tangguh; tegas dan berani; bekerja keras, ikhlas dan cerdas; misi sosial; visioner; pelobi yang handal dan agamis). Kepala sekolah mengembangkan iklim belajar melalui : 1) komitmen dan disiplin waktu; 2) membangun karakter-karakter unggul, 3) kebijakan pembentukan karakter-karakter; 4) iklim belajar potensi prestatif; 5) iklim kerja profesional; 6) hadir berkeliling berinteraksi dengan siswa; 7) salam tegur sapa dalam berbagai aktivitas. Kepala sekolah mengembangkan program pembelajaran dimulai dengan memberikan contoh menjadi profesional pendidik - mengajar layaknya seorang guru, berkomitmen melaksanakan supervisi, memfasilitasi berbagai kegiatan akademik dan pengembangan profesi guru berkelanjutan (IHT, MGMP, Workshop-Workshop). Kepala sekolah berkomitman memandang penting dirinya : hadir, terlibat dan berinteraksi dalam setiap kesempatan, sebagai wujud memberikan perhatian dan dukungannya.